THE PEASANTS COOPERATIVISM IN LA ARAUCANÍA 1963-1973. A MODERNIZATION ATTEMPT OUT OF CONTEXT - Padilla Vilches, Gonzalo Alexis (Revista de Historia Social y de las Mentalidades, 2020)
In the early 1960s a successful peasant cooperative movement was installed in La Araucanía, which, despite its rapid growth, lost importance in the mid-1970s. This article seeks to explain the decline, characterizing cooperative organizations and identifying the problems they faced until 1973. The methodology is based on the analysis of unpublished documentary sources and pertinent literature. In our opinion, although the cooperatives experienced a strong impulse, they did not manage to become a consolidated or predominant model. Rather, as a result of the promotion strategies implemented from the centers of national power, a dependent and weakened regional movement was formed.